Stiff left atrial syndrome after low‐dose radiotherapy for right breast cancer: The need for invasive hemodynamics at exercise. Issue 5 (13th June 2019) - Baratto, Claudia; Caravita, Sergio; Perego, Giovanni B.; Parati, Gianfranco
Abstract: Stiff left atrial (LA) syndrome is a distinct phenotype of heart failure with preserved ejection fraction, characterized by predominant high LA pressure. We describe the case of a middle‐aged woman who developed exertional breathlessness during low‐dose radiotherapy for right breast cancer and who was eventually found to be affected by stiff LA syndrome. Invasive hemodynamics allowed the recognition of pathognomonic tall V waves in the wedge position during exercise, in spite of inconclusive noninvasive investigations.